General Principles of Anti-Corruption in V4 Visegrad Countries: Experience of Hungary - V. S. Makarenko (Law and Safety)
Corruption in Hungary poses a significant risk to business, especially in the tax administration and public procurement sectors, which suffer from its high level. The public procurement process and the tendering process are insufficiently protected from irregularities at the local level due to strong informal relations between business and representatives of government at the local level. Public opinion polls on general and specific corruption issues show that a third of Hungarians consider corruption and abuse of power to be widespread in Hungary’s public administration system.